Physical mapping and YAC contig analysis of the region surrounding Xist on the mouse X chromosome. - Heard, E; Simmler, M; Larin, Z; Rougeulle, C; Courtier, B; Lehrach, H; Avner, P (1993)
The Xist sequence has been proposed as a potential candidate for the X-inactivation center based both on its localization within the candidate region for the X-inactivation center in man and mouse and on its unique pattern of expression from the inactive X chromosome. We have cloned 550 kb of DNA surrounding the mouse Xist sequence in contiguously overlapping YAC clones and have developed a long-range restriction map that spans almost 1 Mb of this region and includes this YAC contig. The detailed restriction map we have established provides a framework for the identification of expressed sequences other than Xist that may equally exhibit unusual expression characteristics associated with X inactivation. The presence of possible structural or methylation differences within this region between the active and inactive X chromosomes has been investigated through comparative analysis of male and female genomic DNA, and we report here the identification of certain CpG-containing restriction sites around Xist that have an interesting differential methylation status on the inactive and active X chromosomes.